2003
DOI: 10.1016/s0886-3350(02)01483-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial endophthalmitis after small-incision cataract surgery

Abstract: The findings suggest that a temporal corneal incision may lead to an increased risk of postoperative endophthalmitis and that the IOL material does not affect the incidence of this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…The clear corneal incision is thought to have contributed to the increase in the number of endophthalmitis cases after phacoemulsification surgery. [36][37][38] Most convincing are the data presented by Nagaki et al, 36 which show an endophthalmitis rate of 0.29 after temporal clear corneal incisions. Their results are not, however, comparable to those in our study because they did not use an intracameral antibiotic agent at the end of surgery.…”
Section: Discussionmentioning
confidence: 92%
“…The clear corneal incision is thought to have contributed to the increase in the number of endophthalmitis cases after phacoemulsification surgery. [36][37][38] Most convincing are the data presented by Nagaki et al, 36 which show an endophthalmitis rate of 0.29 after temporal clear corneal incisions. Their results are not, however, comparable to those in our study because they did not use an intracameral antibiotic agent at the end of surgery.…”
Section: Discussionmentioning
confidence: 92%
“…What is widely accepted is that CCI architecture and selfsealing capacity of the wound play an important role in the development, diagnosis, and treatment of postoperative endophthalmitis. [9][10][11][12] Controlled laboratory models using India ink 13,14 have shown penetration of bacterial-sized particles into the sutureless CCI stromal tunnel and into the anterior chamber. Other studies [15][16][17] found penetration of blood, trypan blue, and antibiotic ointment into the anterior chamber during the immediate postoperative period when sutureless CCIs were used.…”
mentioning
confidence: 99%
“…Although endophthalmitis and early wound-related complications are inherent disadvantages of CCI,[2021] no cases of endophtalmitis were seen in our study. This is in line with the results of Miller et al .…”
Section: Discussionmentioning
confidence: 52%